Open Data for Resilience Initiative : Planning an Open Cities Mapping Project - World Bank Group; Global Facility for Disaster Reduction and Recovery (World Bank, Washington, DC, 2014)
This guide offers a comprehensive understanding of the design and implementation of an Open Cities mapping project for both practitioners in the field and those interested in a higher-level understanding of the process. The guideapos;s content is based on experience in implementing the initial Open Cities projects in Bangladesh, Nepal, and Sri Lanka as well as on previous mapping project experience. Where relevant, it provides relevant examples from those projects in the text and full case studies at the end of guide. The Open Cities Project launched its efforts in three cities: Batticaloa, Sri Lanka; Dhaka, Bangladesh; and Kathmandu, Nepal. These cities were chosen for: 1) their high levels of disaster risk; 2) the presence of World Bank-lending activities related to urban planning and disaster management that would benefit from access to better data; and 3) the willingness of government counterparts to participate in and help guide the interventions. Chapter 2, quot;Project Design and Preparation,quot; covers how a project design process begins: by identifying partners, clarifying a projectapos;s objectives and scope, assembling a team of managers and mappers, and assessing the necessary resources for mapping. Chapter 3, quot;Getting Started,quot; then describes the steps after the initial planning stage: how to locate an appropriate workspace, assess equipment costs, and prepare staff training. Chapter 4, quot;Implementation and Supervision,quot; takes a practical look at data collection techniques from both the organizational and technical perspectives. It also addresses common challenges and mechanisms for quality control and reporting. Finally, chapter 5 examines the lessons learned from previous Open Cities projects and considers future improvements to the overall project design.